Инновационные педагогические технологии и их применение в учебном процессе - Исламгалиева, В.Ж. (My University, 2016)
In this article the autor describes the role of innovative pedagogical technologies in the process of teaching of future specialists. Thus. We consider different features of application and creation of case- method.
Keywords: technology; training; case-study; activity; personality